The OPTIMIZATION OF COUNSELING GUIDANCE BY THE BINMAS UNIT TO PREVENT CRIMES ACTION IN KARANGANYAR POLICE - ABEL GABRIENZAGHY (Police Studies Review, 2022)
This research is motivated by the high number of criminal acts cases in Karanganyar Regency. In recent years the total number of criminal acts was high and has experienced a rapid increase. Repressive efforts have been already, but criminal acts are still often. Therefore, a research was conducted that aims to describe and analyze the optimization of the implementation of counseling activities by the Karanganyar Police Binmas Unit and what collaborations do in the execution of counseling activities by the Karanganyar Police Binmas Unit. This research was conducted with a qualitative approach and using the field research method. the accumulation of data was through interviews, observations, and document studies. The theory used is the theory of Management, the theory of Cooperation and the Concept of Binmas, and the Concept of Counseling Guidance based on Perkap Number. 21 of 2007. The result of the research found that the implementation of guidance and counseling had not run as expected. This is caused by several obstacles in its implementation, including the condition of the Binmas Unit which still has many shortcomings in terms of quality and quantity. Counseling is rarely carried out, as well as external factors such as people who do not care about security and social order and lack of legal awareness by the community itself. The conclusion is that the implementation and cooperation carried out in guidance and counseling activities to prevent criminal acts is not optimal, the authors suggest making SOPs for the execution of counseling guidance that is adapted to current conditions (covid-19), making specific materials packaged in an attractive and varied manner by coordinating with related functions, as well as making policies for the Binmas Unit to carry out formal counseling guidance with the subject matter of related criminal acts.